2008
DOI: 10.1109/led.2008.2000918
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of External Extraction Efficiency in GaN-Based LEDs by $ \hbox{SiO}_{2}$ Nanosphere Lithography

Abstract: A practical approach to fabricate textured GaNbased light-emitting diodes (LEDs) by nanosphere lithography is presented. By spin coating a monolayer of SiO 2 nanoparticles as the mask, textured LEDs can be fabricated. Both textured p-GaN and textured indium tin oxide LEDs show significant improvement over conventional LEDs without damaging the electrical characteristics. The results show that the method is promising for manufacturing low-cost high-efficient GaN-based LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The GaN nanorods were defined by various methods like conventional photolithography, e-beam lithography, and nanoimprint lithography, or other low cost methods, for example, nanoscale self-organized nickel islands as etching mask or SiO 2 nanosphere lithography. [115][116][117][118] Dry etching methods, such as RIE-ICP, were used to achieve high aspect ratio GaN nanopillars.…”
Section: Gan Nanoledmentioning
confidence: 99%
See 1 more Smart Citation
“…The GaN nanorods were defined by various methods like conventional photolithography, e-beam lithography, and nanoimprint lithography, or other low cost methods, for example, nanoscale self-organized nickel islands as etching mask or SiO 2 nanosphere lithography. [115][116][117][118] Dry etching methods, such as RIE-ICP, were used to achieve high aspect ratio GaN nanopillars.…”
Section: Gan Nanoledmentioning
confidence: 99%
“…115,116,118,120 However, using a top-down method, a large portion of GaN material is etched away and does not contribute to light emission any more. This will add additional cost during device fabrication compared to the bottom-up (growth) method.…”
Section: Gan Nanoledmentioning
confidence: 99%
“…They describe the use of spin-coating to texture the LEDs with a monolayer of silica nanoparticles. Their results show that textured p-GaN and indium tin oxide LEDs exhibit significant improvements as compared to conventional LEDs with disparity in electrical characteristics [137]. Kim et al reported …”
Section: Light Emitting Diodesmentioning
confidence: 98%
“…They describe the use of spin-coating to texture the LEDs with a monolayer of silica nanoparticles. Their results show that textured p-GaN and indium tin oxide LEDs exhibit significant improvements as compared to conventional LEDs with disparity in electrical characteristics [137]. Kim et al reported that arrays of silica nanosphere monolayers that were spin-casted onto a polymer layer on top of a GaN surface can result in a hexagonal pattern of nanolenses that was shown to improve the light extraction efficiency of ultra violet LEDs by 23% [138].…”
Section: Light Emitting Diodesmentioning
confidence: 99%
“…Surface passivation with appropriate dielectric layers is also necessary to avoid non-radiative recombination for high η rad [2]. Special techniques such as control of surface roughness [3][4][5], preparation of patterned sapphire substrate (PSS) [6,7], application of flip-chip bonding [8][9][10], adaption of laser lift-off process [11], and formation of photonic crystal structure [12] are frequently used to improve η ext , which can be increased by increasing the critical angle for the emitted light through an appropriate modification of the surface of the LED [13,14]. Anti-reflection (AR) coating of dielectric layers is frequently used to reduce the Fresnel reflection at the semicon-ductor-air interface in communication LEDs.…”
Section: Introductionmentioning
confidence: 99%